Shifting Prevalence of Gallbladder Polyps in Korea - Lee, Yoo Jin; Park, Kyung Sik; Cho, Kwang Bum; Kim, Eun Soo; Jang, Byoung Kuk; Chung, Woo Jin; Hwang, Jae Seok (Journal of Korean medical science, 2014)
Only a few studies have evaluated the population-adjusted prevalence of gallbladder polyps (GBP). This study aimed to evaluate the changes in GBP prevalence and risk factors at a single health screening center in Korea from 2002 to 2012. Of 48,591 adults who underwent health screening between 2002 and 2012, 14,250 age- and gender-matched subjects were randomly selected to evaluate prevalence. Risk factors were analyzed between the GBP-positive and GBP-negative groups during 2002-2004 (Period A) and 2010-2012 (Period B). The annual prevalence of GBP over the 11-yr period was 5.4%. Annual prevalence increased from 3.8% in Period A to 7.1% in Period B. Male gender and obesity were independent risk factors for GBP in both periods. Hepatitis B virus surface antigen (HBsAg) positivity was a risk factor for GBP in Period A but not in Period B. The risk factors for GBP changed from HBsAg positivity to lipid profile abnormalities. Other variables including age, hypertension, diabetes, impaired fasting glucose, chronic hepatitis C virus infection, and liver function tests did not correlate with GBP. In conclusion, GBP prevalence is increasing and risk factors for GBP have changed in Korea. More attention should be paid to this issue in the future.